How Has Digital Transformation Reshaped Personal Financial Management Behavior Research? (Moneter : Jurnal Ekonomi dan Keuangan, 2026)
Personal financial management behavior has gained prominence amid economic globalization, digital transformation, and crisis-induced shifts that reshape individual decision-making, budgeting, saving, and risk practices. This study conducts a comprehensive bibliometric analysis to chart the intellectual structure, growth patterns, and future orientations of research in this domain. Drawing on 312 English-language publications from the Scopus database spanning 2000 to 2024, the analysis employs VOSviewer for co-authorship, keyword co-occurrence, and co-citation mapping, complemented by performance metrics on trends and productivity. Findings reveal a marked acceleration in scholarly output, particularly after 2020, driven by heightened attention to digital tools and resilience factors. Thematic clusters highlight progression from foundational literacy and demographic influences to psychological mediators (e.g., self-efficacy, attitudes) and outcomes centered on well-being and socialization. Geographic contributions concentrate in the United States and Indonesia, with strong Asia-Pacific networks, while productive authors form specialized collaborative hubs. The intellectual base integrates behavioral frameworks with empirical applications, underscoring interdisciplinary depth. These insights address fragmentation in prior work by providing a unified knowledge map, revealing gaps in cross-cultural integration and dynamic digital modeling. Implications extend to guiding targeted interventions for financial education and policy, fostering individual resilience in volatile environments. This synthesis supports scholars and practitioners in advancing evidence-based approaches to sustainable personal finance practices.